Handgrip strength is associated with cognitive function in patients with head injury with loss of consciousness: results from the NHANES 2011–2014 - Bilian Guo; Bilian Guo; Weihui He; Ni Zeng; Xiang Xu; Xiang Xu; Zhipeng Yan; Zhipeng Yan (Frontiers in Neurology)
BackgroundWe evaluated the relationship between handgrip strength (HGS) and cognitive function in patients with head injury with loss of consciousness (HIC) using National Health and Nutrition Examination Survey (NHANES) data.MethodsUtilizing the 2011–2014 NHANES database, we screened participants who completed the HIC questionnaire and extracted relevant variables. Key variable was the sum of maximum bilateral HGS. Cognitive function encompassed global cognitive function, Immediate Recall Test (IRT), Delayed Recall Test (DRT), Animal Fluency Test (AFT), and Digit Symbol Substitution Test (DSST). Weighted multivariate linear regression analyzed the relationship. Gender-stratified analyses explored differences. Restricted cubic spline models elucidated the dose–response curves of HGS on cognitive function.ResultsAmong 283 American HIC patients, HGS significantly correlated positively with global cognitive function, IRT, DRT, and DSST. Gender-stratified analysis showed that HGS enhancement significantly improved DRT and DSST scores in males, while females primarily benefited in Global cognitive function and AFT. Restricted cubic spline analysis confirmed a consistent linear dose–response relationship between HGS and cognitive function indicators, valid in both genders.ConclusionOur study reveals a positive correlation between HGS and cognitive function in HIC patients, with gender differences, offering a novel perspective for cognitive status assessment. Future large-scale, multidimensional studies are needed to deepen understanding of the complex HGS-cognitive function relationship.